Genetic analysis and resistance mechanisms in Anthurium against anthracnose disease caused by Colletotrichum gloeosporioides - Srisamoot, Nattapong; Chomnawang, Piyanan; Wiriyaampaiwong, Piyachat; Teerakun, Mullika; Sootsuwan, Kaewta; Sirisantimethakom, Likit; Tankrathok, Anupong; Srisamoot, Teamjun (Food Agricultural Sciences and Technology, 2026)
The objective of this study was to explore the genetic mechanisms underlying resistance to anthracnose disease in Anthurium cultivars, caused by the fungal pathogen Colletotrichum gloeosporioides. Anthracnose poses a significant challenge to Anthurium cultivation, impacting both yield and ornamental quality. This research aimed to fill the knowledge gap in molecular mechanisms of resistance, focusing on key defense-related enzymes, chitinase and β-1,3-glucanase. The methodology involved collecting ten Anthurium cultivars and performing artificial inoculation with C. gloeosporioides. DNA extraction, polymerase chain reaction, and sequencing were used to investigate genetic traits associated with anthracnose resistance. Enzymatic assays measured chitinase and β-1,3-glucanase activities to assess physiological responses. Data analysis included genetic similarity comparisons to determine genetic closeness among cultivars. Results revealed that Plew Tien Phuket and Plew Tien Lampang showed higher resistance with increased enzyme activity, displaying fewer lesions compared to susceptible cultivars like Merengue. Chitinase and β-1,3-glucanase activities significantly increased in inoculated plants, indicating a robust defense response. Genetic analysis showed significant diversity, with high similarity coefficients between resistant cultivars, highlighting genetic factors contributing to anthracnose resistance. In conclusion, elevated activities of chitinase and β-1,3-glucanase were associated with enhanced resistance to anthracnose, suggesting these enzymes as potential markers for breeding programs. These findings provide valuable insights into the molecular basis of anthracnose resistance, offering a foundation for sustainable disease management in Anthurium cultivation